2021
DOI: 10.1155/2021/8880590
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Long-Term Efficacy of Acupuncture Therapy for Subacute Poststroke Aphasia: Study Protocol for a Randomized, Blinded, Controlled, Multicentre Trial

Abstract: Background. Poststroke aphasia (PSA) is a disabling condition that decreases the quality of life, and the duration of the disease harms the quality of life of PSA patients. Acupuncture has been widely employed for PSA. There is some evidence for the immediate treatment efficacy of acupuncture for PSA; however, long-term results after acupuncture may be poorer. Methods. This is a multicentre, randomized, blinded, nonacupoint (NA) acupuncture controlled, multimodal neuroimaging clinical trial. A total of 48 subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Body acupuncture emphasizes holistic treatment. Body acupuncture can combine syndrome differentiation with meridian differentiation and regulate the mind and Qi [ 123 , 124 ].…”
Section: Acupuncture In Psamentioning
confidence: 99%
“…Body acupuncture emphasizes holistic treatment. Body acupuncture can combine syndrome differentiation with meridian differentiation and regulate the mind and Qi [ 123 , 124 ].…”
Section: Acupuncture In Psamentioning
confidence: 99%
“…18,24,27 It is recommended to verify the location of the catheter tip after insertion, for which there is evidence that ultrasound provides precise information about the position of the device tip. 5,8,11 It is observed that it is incumbent on the nurse to perform the procedures related to Nursing care for the patient using the PICC, being exclusive to this the maintenance of the same -care with the site of insertion, dressing and collection of blood in special situations. It should be emphasized that, when supervised by a trained nurse, the duties of the Nursing technician can perform the irrigation of the PICC / CCIP (flushing) and the administration of intravenous parenteral solutions, safeguarding the particularities of the drug therapy.…”
Section: Category 1 -The Importance Of Nursing Professionals In the Use Of Picc / Ccipmentioning
confidence: 99%
“…18 It is stated that the use of ultrasound with the Seldinger technique contributed to reduce complications and maintenance costs, which was reflected in the improvement of patients' comfort level; therefore, this procedure should be widely used. 11 In conclusion, considering the indications of use and the comfort provided to patients, considering the benefits to the professionals involved in the care, the cost-effectiveness, besides the low complication rates, that the selection of PICC / CCIP in the treatment of patients is an opportune and viable option.…”
Section: Category 1 -The Importance Of Nursing Professionals In the Use Of Picc / Ccipmentioning
confidence: 99%